A functionally conserved homolog of the Drosophila segment polarity gene hh is expressed in tissues with polarizing activity in zebrafish embryos. - Krauss, S.; Concordet, J.P.; Ingham, P.W. (Cell, 1993)
The segment polarity gene hedgehog (hh) encodes a novel signaling protein that mediates local cell-cell interactions in the developing Drosophila embryo. Here we describe the existence of an hh-related gene family in the zebrafish, Brachydanio rerio. One of these genes, sonic hedgehog (shh), is expressed in the notochord, floor plate, and posterior fin mesoderm, tissues associated with polarizing activities in various vertebrate embryos. The pattern of shh expression in zebra-fish mutants affecting axial structures, together with the consequences of its ectopic expression in normal embryos, is consistent with a role for shh in floor plate induction. By expressing shh in transgenic Drosophila embryos, we also demonstrate a strong functional conservation between the fish and fly hh genes.